Indoor localization using Decawave's DWM1001-Dev ultra-wide band device - Ng, Ju Khang (Nanyang Technological University, 2023)
This report presents the development of a dynamic and flexible indoor localization system using Ultra-Wideband (UWB) technology and Decawave DWM1001 devices. With a rapidly growing market, indoor localization systems offer potential in various applications, such as complex indoor navigation. However, traditional methods like GPS, Wi-Fi, Bluetooth Low Energy (BLE), and Radio Frequency Identification (RFID) encounter limitations such as signal obstruction, accuracy, and range limitations within indoor environments. Conversely, UWB has emerged as a promising alternative, offering superior accuracy (less than 10cm) and comparable range to Wi-Fi. This project harnesses UWB's capabilities, utilizing Time of Flight (ToF) and trilateration algorithms to determine the locations of each nodes. Uniquely, the system doesn't tie devices to specific roles, allowing dynamic addition or removal and enhancing flexibility. Each device performs ranging with each other, storing distances in a matrix which can be extracted by a connected gateway through the serial port. This distance matrix helps with visualizing the location of all UWB nodes with the use of a Graphical User Interface (GUI), making a flexible and dynamic indoor localization application.